The relationship of the nurse's knowledge and attitude with Implementation of Patient Safety Goals (Patient Safety) in the Inpatient Room Toto Kabila Hospital - Nur Alwia Bagoe; Nanang Roswita Paramata; Rachmawaty D. Hunawa (Universitas Muhammadiyah Palu, 2026)
Patient safety is an important indicator in the quality of health services in hospitals. Nurses have a major role in the implementation of patient safety goals, which are influenced by knowledge and attitudes. However, there are still incidents that show that the implementation of patient safety in the inpatient room is not optimal. This study aims to determine the relationship between nurses' knowledge and attitudes and the implementation of patient safety goals at Toto Kabila Hospital. This study is a quantitative research with a cross sectional method. A sample of 94 nurses was taken using the Probability Sampling technique with a Stratified Random Sampling approach. This research instrument used a questionnaire on knowledge, attitudes, and implementation of patient safety goals. Bivariate analysis used the Chi-Square test. The results showed a significant relationship between knowledge and the implementation of patient safety goals (p-Value = 0.000). Meanwhile, there is also a significant relationship between attitude and the implementation of patient safety goals (p-Value = 0.000). It is hoped that the hospital can increase training and supervision related to patient safety to improve the quality of service and prevent patient safety incidents.